Adult Patients Affected by Cystic Fibrosis in Therapy with Cystic Fibrosis Transmembrane Regulator Modulators and Lung Transplant: Renal Function, Metabolic and Nutritional Status. (30th November 2020) - Lai, Silvia; Mazzaferro, Sandro; Mitterhofer, Anna Paola; Tinti, Francesca; Bonci, Enea; Giovannetti, Antonello; Casella, Claudio; Perrotta, Adolfo Marco; Bagordo, Domenico; Murciano, Manuel; Galani, Alessandro; Celani, Camilla; et al.
Abstract : Background . Cystic fibrosis (CF) is one of the most frequent genetic diseases. The discovery and implementation of new therapies prolonged the survival of CF patients in the last years. Evaluation of long-term complications could be useful to improve the outcome of these patients. Aim of the Study . To evaluate renal function, metabolic, nutritional, and inflammatory status in CF patients on cystic fibrosis transmembrane regulator (CFTR) modulators therapy as well as lung transplant recipients (LRs) and patients on conservative therapy (control group). Materials and Methods . We performed a prospective, longitudinal study on 69 CF patients. Clinical and laboratory parameters (metabolic and nutritional indices and inflammatory markers) were evaluated in all patients before starting CFTR therapy or transplant (T0) and after 3 years (T1). Results . We enrolled 69 CF patients (42 males). Patients were distributed into three groups. The average age was 35.01 ± 10.57 years for the control group (group 0), 32.47 ± 9.40 years for patients on CFTR modulators therapy (group 1), and 38.93 ± 7.14 years for LRs (group 2). At T1, we showed a significant difference among the three groups in terms of renal function indices: creatinine, eGFR, serum nitrogen as well as serum uric acid, sodium, and potassium (p < 0.001, p < 0.001, p < 0.001, p < 0.001, p < 0.001, and p < 0.001, respectively), particularly in LRs patients. Significant differences were found in nutritional status parameters among the three groups: total protein, serum albumin, serum fibrinogen, serum transferrin, and white blood cell counts (p < 0.001, p = 0.037, p = 0.04, p = 0.003, and p = 0.007, respectively), particularly in LRs compared with other groups. Moreover, we found significant differences in metabolic profile (HbA1c, p = 0.026 ) and inflammatory status, with a significant difference in C-reactive protein values, neutrophil counts, and neutrophil-lymphocyte ratio (NLR) among the three groups (p < 0.001, p = 0.005, and p = 0.026, respectively). Conclusions . Our study showed a reduced renal function and poor nutritional status in LRs, along with worse metabolic control. Moreover, we showed a lower inflammatory status in patients on CFTR modulators therapy. Therefore, we suggest early and careful monitoring of renal function, metabolic, and nutritional parameters in CF patients, whether they are on conservative therapy, CFTR modulators therapy, and LRs patients.